TLR3 activation in astrocytes attenuates the nigrostriatal pathway degeneration in rodent models of Parkinson’s disease - Jeong, Jaeyeong; Won, So-Yoon; Chung, Young Cheul; Shin, Won-Ho; Jin, Byung Kwan; Park, Eun S. (Frontiers in Cellular Neuroscience, 2026)
Toll-like receptor 3 (TLR3) is classically known for mediating inflammatory pathways in Parkinson’s disease (PD). However, the role of TLR3 in nigrostriatal degeneration in PD remains unclear. Here, we observed that TLR3 is predominantly expressed on astrocytes in the substantia nigra in both human PD brain and in rat PD models induced by intra-MFB injection of 1-methyl-4-phenylpyridinium (MPP+). Interestingly, Poly I: C, an activator of TLR3, significantly induced TLR3 expression on astrocytes. Treatment with Poly I: C markedly attenuated nigral dopamine neuron death in the PD rat models. The survival of dopamine neurons was accompanied by the production of ciliary neurotrophic factor and vascular endothelial growth factor-B on astrocytes in Poly I: C-treated PD rats. The attenuation of dopamine neuron death was also observed in the Poly I: C-treated AAV2-hα-syn-A53T-induced rat PD model. Our findings suggest that activating TLR3 in astrocytes could be a potential therapeutic strategy for attenuating PD progression.